Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/pace.14104
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a 3D mapping benchmark for ablation in patients with atrioventricular nodal reentrant tachycardia

Abstract: Background: Avoiding excessively fast junctional rhythm (JR) during slow pathway (SP) modification for atrioventricular nodal reentrant tachycardia (AVNRT) helps prevent serious atrioventricular block. This study investigated the usefulness of a predictive ablation point that lies near the boundary line between appropriate and excessively fast JRs with three-dimensional (3D) electroanatomical mapping in AVNRT patients. Methods: Participants were 141 consecutive patients with common AVNRT who received anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Bhaskaran et al reported on their experiences with an EMS in 30 patients and showed a safe ablation distance to His bundle region of >25 mm ( 22 ). Yamamoto et al reported on the implementation of a predictive ablation point in an EMS resulting in simplification and improvement of their ablation procedures ( 23 ). In our study we found a significant reduction of FT and DAP using EMS/FIS.…”
Section: Discussionmentioning
confidence: 99%
“…Bhaskaran et al reported on their experiences with an EMS in 30 patients and showed a safe ablation distance to His bundle region of >25 mm ( 22 ). Yamamoto et al reported on the implementation of a predictive ablation point in an EMS resulting in simplification and improvement of their ablation procedures ( 23 ). In our study we found a significant reduction of FT and DAP using EMS/FIS.…”
Section: Discussionmentioning
confidence: 99%